Preguntas Frecuentes Acerca de la Abeja Melífera Africanizada en Florida - Michael K. O'Malley; James D. Ellis; P. Herrera; Anita S. Neal (EDIS)
Revised! ENY-140S, a 3-page fact sheet by M. K. O’Malley, J. D. Ellis, P. Herrera, and A. S. Neal, is the Spanish language version of ENY140/IN738 Frequently Asked Questions about the Africanized Honey Bee in Florida. It provides information about Africanized honey bees (AHB) in a question-and-answer format. Published by the UF Department of Entomology and Nematology, August 2010.